Analisis Kualitas Pelayanan Publik pada Kantor Pelayanan Perizinan dan Penanaman Modal (KP3M) Kabupaten Solok - Fitri, Suci Emilia (TINGKAP, 2012)
Public service is a thing which must be implemented and complied optimally by a Government to satisfy the wishes and needs of the community. The number of complaints on the catapult of public opinion on the public service by the Government at least be able to portray the state of the quality of public service that currently enjoy the community. This study will analyze the quality of public service and the factors that may effect the quality of public services in the office of licensing and investment services (KP3M) Solok Regency.This study used a qualitative descriptive approach. The data were collected through interviews, observation, and documentation study. The finding of this study showed that the quality of care licensing in the District of Solok KP3M is not good enough. It can be seen from the state office buildings are not adequate services, lack of support facilities and services have not explained the procedure and the completion time of licensing services. While service quality is good enough permissions can be seen from the attitude of employees KP3M in serving the community. In addition there are several factors that effect the poor quality of the services license KP3M Solok regency, such as technology of information and communication, culture and social environment